Effect of Addition of Betel Leaf Decoction on Survival Rate of Goldfish Infected with Dactylogyrus sp. - Rizky Saputra; Ade Muharam; Syamsuddin Syamsuddin (The NIKe Journal, 2020)
This study aims to determine the effect of adding boiled betel leaf (Piper bettle Linn) with different doses on the survival rate of goldfish (Cyprinus carpio) infected with Dactylogyrus sp. This research was conducted at the Laboratory of the Fish Quarantine Station, Quality Control and Safety of Class I Fishery Products, Gorontalo. This study used an experimental method with a completely randomized design (CRD), 4 treatments and 3 replications. The test method is by soaking the betel leaf stew for 30 minutes. With dosage. Treatment A (control), B (5 ml / L water), C (10 ml / L water), D (15 ml / L water). Observations include the survival of goldfish. Treatment A (86.7%), B (100%), C (93.3%), and D (86.7%), parasite intensity and density of Dactylogyrus sp., observation of clinical symptoms and water quality. The data analysis used was the Analysis of Variance (ANOVA). The results showed that the treatment of giving betel leaf stew with different doses on the survival of goldfish infected with the parasite Dactylogyrus sp had no significant effect among treatments. Water quality parameters during the study were still in normal conditions for the life of goldfish seeds. Keywords: Goldfish; betel leaf; survival rate; Dactylogyrus sp.